Small spaces have large impacts: Microsites determine plant litter decomposition rates in drylands - Heather L. Throop; Marie-Anne de Graaff; Jayne Belnap (Proceedings of the National Academy of Sciences, 2025)
Our understanding of carbon and nutrient dynamics in globally vast and socioeconomically critical dryland ecosystems lags behind mesic systems. Litter decomposition models consistently underestimate measured decomposition in these regions. Both models and measurements largely represent spatially dominant intercanopy areas; however, little litter resides in these interspaces as transport vectors move litter to other microsites such as beneath plant canopies and buried in soil. Abiotic and biotic conditions differ among microsites, but few studies have characterized microsite impacts on decomposition. We collated data on microsites where litter accumulates. In microsites with sufficient available data, we used meta-analysis to test hypotheses on decomposition relative to litter in intercanopy spaces. Decomposition was lower under woody plant canopies than in intercanopy spaces. Buried litter decomposed faster than surface litter. There was no difference in decomposition between surface litter and litter suspended aboveground to simulate standing dead. All microsite contrasts had exceptions, suggesting that site-specific characteristics influence microclimate and subsequent decomposition. Extrapolation of decomposition rates to the landscape-level (using estimates of microsite-specific decomposition rates multiplied by litter pools), suggests that decomposition estimates based on intercanopy data alone underrepresent landscape-level decomposition. Thus, despite advances in the understanding of mechanistic decomposition drivers in drylands advancing, most studies are spatially unrepresentative analyses in intercanopy areas and this will underestimate decomposition at the landscape level. Expanding the ecological relevance of decomposition processes to be useful for predicting larger-scale carbon and nutrient dynamics requires improved characterization of dryland litter distribution, coupled with a mechanistic understanding of decomposition in microsites where litter accumulates.